Regverdiging van die sondaar: Martin Luther se teologiese definisie van die mens soos uiteengesit in die Disputatio de homine van 1536, stelling 32 - Wyk, Gabriël M. J.van (HTS teologiese studies, 2017)
Disputations were a fixture of Martin Luther’s academic career. Luther participated regularly in disputations. It was an important communicative vehicle through which he developed and expressed his theology. The well-known 95 theses are a case in point. Luther’s career as a disputator was impressive. Several of his most influential disputations were explicitly intended for consideration by his academic and ecclesiastical colleagues, but the majority of his disputations took place as a curricular exercise at the University of Wittenberg. The purpose of these disputations was pedagogical and polemical. Luther deployed the same tools for his defence of proper doctrine that were at the centre of the Protestant reformation in the face of objections. The disputatio de homine is a systematic summary of Luther’s anthropology. It incorporates the doctrine of justification as the theological definition of man. It treats the subject within the context of the relationship between theology and philosophy, and reflects upon the new language of theology. The disputatio de homine provides an essential resource for the study of Luther’s anthropology and the doctrine of justification.